2021
DOI: 10.1111/1462-2920.15829
|View full text |Cite
|
Sign up to set email alerts
|

Complex co‐evolutionary relationships between cicadas and their symbionts

Abstract: Summary Previous evidence suggests that cicadas lacking Hodgkinia may harbour the yeast‐like fungal symbionts (YLS). Here, we reinforce an earlier conclusion that the pathogenic ancestor of YLS independently infected different cicada lineages instead of the common ancestor of Cicadidae. Five independent replacement events in the loss of Hodgkinia/acquisition of YLS and seven other replacement events of YLS (from an Ophiocordyceps fungus to another Ophiocordyceps fungus) are hypothesised to have occurred within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The primers for the amplification of mitochondrial gene (i.e., COI, COII, Cytb) were the same as previously described (24). Multiple alignments of the nucleotide sequences of both cicada and their obligate symbionts were conducted using the online MAFFT program (https://mafft.cbrc.jp/alignment/server/index.html, accessed on 28 July 2022).…”
Section: Phylogenetic Relationships Of Sulcia and Yls In Cicadasmentioning
confidence: 99%
See 2 more Smart Citations
“…The primers for the amplification of mitochondrial gene (i.e., COI, COII, Cytb) were the same as previously described (24). Multiple alignments of the nucleotide sequences of both cicada and their obligate symbionts were conducted using the online MAFFT program (https://mafft.cbrc.jp/alignment/server/index.html, accessed on 28 July 2022).…”
Section: Phylogenetic Relationships Of Sulcia and Yls In Cicadasmentioning
confidence: 99%
“…The molecular phylogenetic analysis uncovered that YLS of cicadas form a clade within the entomoparasitic fungi of the genus Ophiocordyceps, which is regarded as a beneficial symbiont evolved from a pathogenic microorganism [9]. Recently, it was revealed that there were five independent replacement events in the loss of Hodgkinia/acquisition of YLS and seven other separate replacement events of YLS (from an Ophiocordyceps fungus to another Ophiocordyceps fungus) within the sampled taxa of Cicadidae [24]. Genome sequencing of YLS of Meimuna opalifera revealed that the genome of YLS encodes biosynthetic pathways for synthesizing almost all essential amino acids and other nutrients, which is sufficient to compensate for the nutritional services provided by Hodgkinia [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cicada species bear the coresident bacterial symbiont Candidatus Hodgkinia cicadicola (hereafter Hodgkinia) in bacteriocytes of the bacteriomes, which can provide the remaining two EAAs for the host cicadas (McCutcheon et al, 2009a(McCutcheon et al, , 2009bMcCutcheon & Moran, 2010). However, Hodgkinia in some cicada lineages has been replaced by yeast-like fungal symbionts (YLS) harboured in bacteriocytes of the fat bodies (Matsuura et al, 2018;Wang et al, 2022;Wang, Huang, et al, 2021), which is presumed to be able to synthesize almost all the EAAs, vitamins and other metabolites for the host cicadas (Matsuura et al, 2018). During the vertical transmission process, the bacteriome-associated symbionts, especially Sulcia, exhibit extreme shape changes when exocytosed from the bacteriomes to the haemolymph and finally migrate into the terminal oocytes of ovaries (Campbell et al, 2018;Huang et al, 2020;Matsuura et al, 2018;Wang, Huang, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Following at least 250 million years of strict host-association, Sulcia genomes from distantly related hosts show almost perfect gene co-linearity and very similar gene sets ( Moran et al 2005b ; Bennett and Moran 2015 ) [although a broader sampling of Auchenorrhynchan insects shows that several genomic inversions have occurred in different Sulcia lineages ( Deng et al 2022 )]. Likewise, while several cicada groups have replaced Hodgkinia with fungal endosymbionts, Sulcia is retained in every cicada species examined to date ( Matsuura et al 2018 ; Wang et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%